Implementasi Jaringan Syaraf Tiruan dan Pengolahan Citra untuk Identifikasi Jenis Karang - Salambue, Roni (Jurnal Pilar Sains, 2006)
The research is using the implementation of artificial neural network (ANN) to identify the type of coral from digitalimage. An ANN is an information-processing system that has certain performance characteristics in cnmon withbiological neural networks. ANN have been developed as general izatons of mathematical models of neural biology,input to ANN are color and shape information from image. For the extraction of the information, the methods ofimage processing is used which are RGB and HSV color model and moment invarian for shape.